PENGARUH PENERAPAN METODE PEMBELAJARAN JARAK JAUH TERHADAP HASIL BELAJAR SISWA DI SD NEGERI 5 RANOMEETO, KAB. KONAWE SELATAN - Ilham, Muhammad; Agus, Imaludin; Kadir, Sitti Fatimah; Nursagita, Yuni (Jurnal keilmuan dan Kependidikan dasar, 2022)
Distance learning, which is the only alternative to learning during the pandemic, is faced with various problems that arise in the field. This research was conducted to examine the portrait of distance learning at SD Negeri 5 Ranomeeto and to see the effect of the use of distance learning methods on student learning outcomes at the school. This study employed quantitative research with a survey approach. The total population was 40 students with a saturated sampling technique. Data on distance learning conditions at SDN 5 Ranomeeto were collected through interview and observation methods. Meanwhile, data on distance learning methods were collected using a questionnaire, and data on learning outcomes was obtained from students' daily test scores. Data analysis was carried out by means of qualitative descriptive analysis and inferential statistical analysis consisting of classical assumption test, while hypothesis testing used a simple linear regression test. The results of this study indicate that distance learning at SD Negeri 5 Ranomeeto utilizes the WhatsApp application. This learning provides a lot of time for students to take part in learning, but parents consider that the use of the WhatsApp application in distance learning is less effective and students quickly feel bored participating in learning. The distance learning method has a significant effect on student learning outcomes with the t-count value greater than the t-table value (8.818 > 2.024).